2020 survey of Australian orthodontists' procedures - Miles Peter; Freer Elissa; Ong Desmond (Sciendo, 2020)
This second survey of Australian Society of Orthodontists members was conducted to assess their treatment preferences and compare with the results of the 2013 survey.